Front Cover: Two‐Step Thermal Annealing: An Effective Route for 15 % Efficient Quasi‐2D Perovskite Solar Cells (ChemPlusChem 8/2021). Issue 8 (14th June 2021) - Romano, Valentino; Najafi, Leyla; Sutanto, Albertus Adrian; Schileo, Giorgio; Queloz, Valentin; Bellani, Sebastiano; Prato, Mirko; Marras, Sergio; Nazeeruddin, Mohammad Khaja; D'Angelo, Giovanna; Bonaccorso, Francesco; Grancini, Giulia
Abstract : The Front Cover shows the crystal structure of a Ruddlesden‐Popper quasi‐2D perovskite with chemical formula (PEA)2 MA39 Pb40 I121 (with PEA: phenylethylammonium and MA: methylammonium). The subscript 40 indicates the number of PbI6 octahedra separated by a double layer of PEA cations. Such quasi‐2D perovskites exhibit efficient photovoltaic performances and higher stability with respect to the pure 3D counterpart (MAPbI3 ). More information can be found in the Communicaton by G. Grancini, M. K. Nazeeruddin, and co‐workers .